REFUSAL APPLIED IN "ALADDIN MOVIE" - Sri Intan Malina Putri; Ambalegin Ambalegin (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2022)
This descriptive qualitative research discovered to investigate the types of refusal in Aladdin movie. This movie was modified by the folklore Aladdin in the Walt Disney Pictures, the folklore was made by Terry Rossio. Then, there were the types of refusal, namely indirect refusal, direct refusal, and adjunct refusal. This study was applied the theory by Felix brasdefer, (2008) and Houck, (1999). The most common reason for using indirect refusal than direct and adjunct refusal because it can minimize the negative effect (FTA) of the hearer. This research was using an observational method and a non-participatory method by Sudaryanto's theory. Then, the data was analyzed using the pragmatics identity method. Meanwhile, the finding results of frequently of this research were found 21 data of indirect refusal, 13 data of direct refusal, and 9 data of adjunct refusal. Based on data source, the character of Aladdin mostly used indirect refusal statement.